The Robotarium: Automation of a Remotely Accessible, Multi-Robot Testbed - Wilson, Sean; Glotfelter, Paul; Mayya, Siddharth; Notomista, Gennaro; Emam, Yousef; Cai, Xiaoyi; Egerstedt, Magnus (IEEE robotics and automation letters, 2021)
The cost, in terms of both time and money, of instantiating a physical testbed can be prohibitive. To help resolve this issue, the Robotarium offers a free, remotely accessible robotics lab to users around the world. Since allowing the general public to use it, hundreds of users have submitted thousands of experiments. The current and accelerating experiment submission rate poses an operational challenge that cannot be handled through manual or human supervised execution without devoting a full time operator to the platform. A solution to this problem is enable the Robotarium to operate autonomously: improving the robustness and reliability of the system while reducing required human intervention to diagnose and recover from failures. In this pursuit, the hardware, software, and algorithms deployed on the Robotarium have undergone numerous developments, including a new differential-drive robot, the use of modern virtualization techniques for the software infrastructure, and the inclusion of robust constraint-satisfaction methods for long-term safe operation. Over the past year of autonomous operation, these advances have resulted in 0.76% of the 3402 submitted remote experiments failing and requiring human intervention to recover from. This paper details these development efforts and best practices that have been learned automating a remote-access testbed to keep up with the experimental demand of a large, active, and growing userbase.